2021
DOI: 10.3390/brainsci11091226
|View full text |Cite|
|
Sign up to set email alerts
|

A Lifespan Development Theory of Insecure Attachment and Internalizing Symptoms: Integrating Meta-Analytic Evidence via a Testable Evolutionary Mis/Match Hypothesis

Abstract: Attachment scholars have long argued that insecure attachment patterns are associated with vulnerability to internalizing symptoms, such as depression and anxiety symptoms. However, accumulating evidence from the past four decades, summarized in four large meta-analyses evaluating the link between insecure attachment subtypes and internalizing symptoms, provide divergent evidence for this claim. This divergent evidence may be accounted for, at least in part, by the developmental period under examination. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 167 publications
(200 reference statements)
0
7
0
Order By: Relevance
“…We also did not assess the potential distinct quality of disorganization attachment's secondary classifications (i.e., disorganized‐secure and disorganized‐insecure). Whereas such fine‐tuned endeavors require a significantly larger sample size, it may be crucial in fine‐tuning potential etiological models given the divergent meta‐analytic and longitudinal links the two organized insecure attachment subcategories have shown in predicting internalizing and externalizing behavioral problems (Dagan et al., 2021; Dagan & Bernard, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We also did not assess the potential distinct quality of disorganization attachment's secondary classifications (i.e., disorganized‐secure and disorganized‐insecure). Whereas such fine‐tuned endeavors require a significantly larger sample size, it may be crucial in fine‐tuning potential etiological models given the divergent meta‐analytic and longitudinal links the two organized insecure attachment subcategories have shown in predicting internalizing and externalizing behavioral problems (Dagan et al., 2021; Dagan & Bernard, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This ambiguous loss continues to disrupt the child's life by making their ability to grieve the loss complicated and confusing. This feeling of loss can often result in shaping a child to believe they are unlovable, with poor self‐worth and difficulty establishing closeness with others (Dagan et al, 2021). Thus, the relationship between the adult child and their partners is also impacted by the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A full understanding of the association may require consideration of the distinction between the disorganized-secure and disorganized-insecure types of categorization. As Dagan et al [ 22 ] point out, this would require a large sample size, but it may be essential for fine-tuning potential etiological models, as the links between the two organized insecure attachment subcategories identified in meta-analytic and longitudinal studies have suggested different models for internalizing and externalizing behavioral problems [ 28 , 29 ].…”
Section: Intergenerational Transmission and The Internal Working Mode...mentioning
confidence: 99%